2012
DOI: 10.1124/jpet.112.194159
|View full text |Cite
|
Sign up to set email alerts
|

Naltrindole Inhibits Human Multiple Myeloma Cell Proliferation In Vitro and in a Murine Xenograft Model In Vivo

Abstract: It has been demonstrated previously that immune cell activation and proliferation were sensitive to the effects of naltrindole, a nonpeptidic ␦-opioid receptor-selective antagonist; therefore, we hypothesized that human multiple myeloma (MM) would be a valuable model for studying potential antineoplastic properties of naltrindole. [3 H]naltrindole exhibited saturable, low-affinity binding to intact human MM cells; however, the pharmacological profile of the binding site differed considerably from the propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The cell proliferation and viability was detected using Vi-Cell XR cell viability analyzer (Beckman Coulter, USA) as previously described (26 , 27) . This technique detects the cell number and cell viability by applying trypan blue dye-exclusion staining combined with image-based data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The cell proliferation and viability was detected using Vi-Cell XR cell viability analyzer (Beckman Coulter, USA) as previously described (26 , 27) . This technique detects the cell number and cell viability by applying trypan blue dye-exclusion staining combined with image-based data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, employing pharmacophore‐based molecular modeling, we have rationally designed and synthesized series of trisubstituted triazoles as novel delta opioid receptor ligands 6,7 . More recently, we reported that NTI inhibited the growth of human U266 cancer cells in vitro and in vivo in a mouse xenograft model, by an opioid receptor independent mechanism 5 . Consequently, several of the triazole analogs, including MM902, were tested for their effects on the growth of human U266 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that naltrindole (NTI), a selective delta opioid receptor antagonist, inhibited human multiple myeloma cell growth in vitro (EC 50 = 18.5 μmol/L) and exhibited efficacy in a mouse xenograft model, by interaction with non-opioid receptor targets. 5 Employing pharmacophore-based molecular modeling of NTI analogs, we have rationally designed and synthesized a series of trisubstituted triazoles as new delta opioid receptor ligands, 6,7 which in turn have led to the discovery of a novel compound MM902 l showing no appreciable binding affinity to opioid receptors ( Figure 1).…”
Section: Recent Development Of Immunotherapy and Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Naltrindole inhibited the increase in phosphorylation of MAPK by DADLE in PC12h cells ( Figure 7 ) and that of both Akt and MAPK in F11 cells ( Figure 6 ), indicating that DADLE may act through the Oprd1 to induce its effect. We observed that F11 cells did not survive in 100 μM of naltrindole for 24 h. This is most likely because high concentration of naltrindole blocked the basal survival PI3K/Akt signaling [ 8 , 46 ], resulting in apoptotic death of F11 cells. To see if the increase in Akt phosphorylation after 24 h of DADLE treatment on F11 cells differentiated in the presence of NGF is specific to the presence of NGF, the cells were treated with 100 nM K252a before adding DADLE for 24 h of treatment.…”
Section: Resultsmentioning
confidence: 99%